Hybrid theranostic microbubbles for ultrasound/photoacoustic imaging guided starvation/low-temperature photothermal/hypoxia-activated synergistic cancer therapy. Issue 45 (2nd November 2021) - Tian, Feng; Zhong, Xingjian; Zhao, JunKai; Gu, Yutian; Fan, Yadi; Shi, Fan; Zhang, Yu; Tan, Youhua; Chen, Wen; Yi, Changqing; Yang, Mo
Abstract : A hybrid microbubble-based theranostic platform was developed for imaging-guided synergistic tumor therapy by combining starvation therapy, low-temperature photothermal therapy (PTT), and hypoxia-activated therapy. Abstract : Constructing a theranostic agent for high-contrast multimodality imaging-guided synergistic therapy with long-term tumor retention and minimum systemic side effects still remains a major challenge. Herein, a hybrid microbubble-based theranostic platform was developed for dual-modality ultrasound (US) and enhanced photoacoustic (PA) imaging-guided synergistic tumor therapy by combining starvation therapy, low-temperature photothermal therapy (PTT), and hypoxia-activated therapy, based on polydopamine (PDA) doped poly(vinyl alcohol) microbubbles loaded with glucose oxidase (GOx) (PDA–PVAMBs@GOx) and hypoxia-activated prodrug (HAP) tirapazamine (TPZ). For dual-modality US/enhanced PA imaging, PDA–PVAMBs provided 6.5-fold amplified PA signals relative to freely dispersed PDA nanoparticles (PDA NPs). For synergistic cancer therapy, oxygen (O2 ) carried by PDA–PVAMBs@GOx was first released to promote starvation therapy by loaded GOx. Then, moderate near-infrared (NIR) laser irradiation triggered PTT and improved enzymatic activity of GOx with its optimal activity around 47 °C. Subsequently, GOx-mediated tumor starvation depleted O2 and exacerbated the hypoxia environment, thereby activating the toxicity of TPZ in the tumor site. Through dual-modality US/PA imaging monitoring, PDA–PVAMBs@GOx with long-term retention (∼7 days) combined with PTT and TPZ significantly inhibited the growth of solid tumors with minimum systemic side effects, which might be a powerful tool for effective tumor treatment.